Hambatan Penegakan Hukum Terhadap Pelaku (Illegallogging) Serta Upaya Penanggulangannya Di Kabupaten Malaka Wilayah Hukum Pengadilan Negeri Atambua - Manek, Ordianus; Pello, Jimmy; Manuain, Orpa G (Law Faculty, Nusa Cendana University, 2023)
Illegal logging is a criminal act that occurs in the forestry sector which has become a national and international issue. Illegal logging is included in a special criminal offense. The legal basis governing the criminal act of illegal logging is Law of the Republic of Indonesia Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction. The formulation of the problem in this study: (1) What are the obstacles faced by law enforcement in enforcing the law against perpetrators (illegal logging) in Malacca Regency?, (2) What is the impact of regulating the function of the Civil Service Police on public order? This research is an empirical legal research that is descriptive. Research location in Upt. Malacca District Forest Management Unit, Malacca Regency Resort Police and Atambua District Court Class 1 B Belu Regency. Management The type of data used includes primary data and secondary data. The data collection techniques used include interviews and literature research in the form of books, laws and regulations, documents, and so on. Data analysis uses qualitative analysis with interactive models. There are also factors that become obstacles to law enforcement against illegal logging crimes, according to Soerjono Soekanto, that the effectiveness or failure of law enforcement is determined by five factors, namely the legal factors themselves (laws), law enforcement factors (parties who form or implement the law), factors of facilities or facilities that support law enforcement, community factors. The results of research in this thesis show that obstacles in law enforcement against illegal logging crimes are minimal legal awareness, inadequate supporting facilities or facilities, insufficient operational costs, no forest police personnel, forestry civil servant investigators. The efforts made by law enforcement are preemptive, preventive and repressive efforts. By cracking down on reports from the public. The researchers' suggestions for the results of this research need to increase legal counseling to the community, procurement of supporting facilities, submitting applications for forest rangers and civil servant investigators, conducting routine joint operations in forest areas, and law enforcement commitment.